NOTARY SERVICE IN THAILAND - Yaya Kareng; Ong Argo Victoria; R. Juli Moertiyono (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2019)
In most countries, a Notary Public is known as an official who is licensed by the State to perform functions such as the authentication of signatures or documents, and the witnessing of affidavits or statements of persons under oath. Notarization of a document is important as the act of notarization itself creates a guarantee on the authenticity of the document, or to the act of the signatories to the instrument. While there are no notaries public in Thailand, some lawyers are given the authority to function as Notarial Services Attorney in the country. In Thailand, it is the Lawyers Council of Thailand which regulates the practice of notarial services in the State. A Thai lawyer is required to undergo and pass a professional training course for the service before he is registered as a Notarial Services Attorney.Keywords: Notary; Service; Attorney; Thailand.